Chagas disease - Weiss, Louis M.; Tanowitz, Herbert B.; Kirchhoff, Louis V. (Amsterdam : Academic, 2011)
This thematic volume provides authoritative, up-to-date reviews addressing recent advances as well as an overview for the research and clinical communities on the endemic infection of Chagas disease. Lead researchers discuss epidemiology and control measures as well as various diagnosis techniques, treatments, and therapies currently being used. The text includes a history of Chagas disease and an outlook for the next century. Informs and updates on all the latest developments in the field Contributions from leading authorities and industry experts.
pt. B. Bioactive lipids in trypanosome cruzi infection / Fabiana S. Machado, et al -- Mechanisms of host cell invasion by trypanosome cruzi / Kacey L. Caradonna and Barbara A. Burleigh -- Gap junctions and Chagas disease / Daniel Adesse, et al -- The vasculature in Chagas disease / Cibele M. Prado, et al -- Infection-associated vasculopathy in experimental Chagas disease: pathogenic roles of endothelin and kinin pathways / Julio Scharfstein and Daniele Andrade -- Autoimmunity / Edecio Cunha-Neto, et al -- ROS signaling of inflammatory cytokines during trypanosome cruzi infection / Shivali Gupta, et al -- Inflammation and Chagas disease: some mechanisms and relevance / Andre Talvani and Mauro M. Teixeira -- Neurodegeneration and neuroregeneration in Chagas disease / Marina V. Chuenkova and Mercio PereiraPerrin -- Adipose tissue, diabetes and Chagas disease / Herbert B. Tanowitz, et al.
Elsevier
Keywords: Chagas' disease; Chagas' disease; Electronic books